Polymer network hole transport layers based on photochemically cross-linkable N′N′-diallyl amide tri-N-substituted triazatruxene monomers. Issue 16 (23rd February 2018) - Hu, Guang; Kitney, Stuart P.; Kelly, Stephen M.; Harrison, William; Lambert, Brian; O'Neill, Mary
Abstract : Novel triazatruxenes, incorporating non-conjugated dienes as photopolymerisable endgroups attached by flexible sidechains to the aromatic core, have been synthesised as a new class of hole-transport layer for plastic electronic devices. Abstract : Novel phtotpolymerisable hole-transport layers based on novel triazatruxenes incorporating six non-conjugated dienes as photo cross-linkable end-groups attached to flexible, aliphatic spacers have been synthesised using simple one-step substitution reactions. Hole-only test devices, fabricated using a combination of solution-deposition, spin-coating and initiator-free photochemical cross-linking of these photopolymerisable triazatruxenes, exhibit almost identical current density vs. voltage profiles before and after cross-linking, and as such, represent a promising new class of hole-transport layer for plastic electronic devices.